Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.6002/ect.2011.0101
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C as a Marker of Glomerular Filtration Rate in Voluntary Kidney Donors

Abstract: Objectives: Cystatin C is emerging as an endogenous marker of glomerular filtration rate. This study sought to assess the usefulness of serum cystatin C as a marker of glomerular filtration rate in comparison with serum creatinine and serum creatinine-based glomerular filtration rate estimations in voluntary kidney donors. 99m Tc-DTPA double plasma sampling method. Glomerular filtration rate-double plasma sampling method was used as a reference value. Results were expressed as means ± SD. Results: The mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Similar observations have been published for cystatin C in the setting of kidney transplantation [17,21] being superior to creatinine in detecting changes in kidney function. However, other studies failed to show superiority of cystatin C as well as NGAL over creatinine in reflecting renal function in different settings [22,23,24,25,26]. Additionally, cystatin C concentrations were observed to rise again in the postoperative period after renal transplantation independently from renal function [21,27], therefore limiting its use under these clinical circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been published for cystatin C in the setting of kidney transplantation [17,21] being superior to creatinine in detecting changes in kidney function. However, other studies failed to show superiority of cystatin C as well as NGAL over creatinine in reflecting renal function in different settings [22,23,24,25,26]. Additionally, cystatin C concentrations were observed to rise again in the postoperative period after renal transplantation independently from renal function [21,27], therefore limiting its use under these clinical circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…With the discovery of cystatin C [25], a potentially superior marker [26], [27], the equations based on it gradually created and popularized.…”
Section: Discussionmentioning
confidence: 99%
“…Large amount of studies have shown that CysC is superior to SCr in predicting the function of kidney [14][18]. Therefore, CysC has been used as an alternative endogenous serum marker of GFR [19], and many formulas for GFR estimation have been developed based upon serum CysC determination [20], [21]. However, these formulas were all established based on a small sample and outside of a laboratory, and the “gold standard” measurement of GFR and CysC is also very inconsistent.…”
Section: Introductionmentioning
confidence: 99%